A Study of Asphyxial Deaths (Medico Legal Update, 2019)
An increasing death rate as a result of violence constitutes a large group in medicolegal autopsies. Specially,deaths due to asphyxia are one of the most important causes in violence deaths.During the 5-year period from January 2013 to October 2018, there were 134 asphyxial deaths autopsiedby the Department of Forensic Medicine, ACSR Government Medical College,Nellore . Asphyxial deathscomprise 15.7% of all forensic autopsies; 20.8% of the cases are aged between 30 and 39 years, and theaverage age was 41.9 years. Males constitute 79.8% of all the cases.The most frequent method of asphyxiation death is hanging (56 cases, 61.8%), followed by drowning(32.6%) and More violent methods, such as ligature or manual strangulations, constitute 3.1% and 2.5% ofall asphyxial deaths, respectively. Although it was varying according to the methods of asphyxiation, suicidewas found to be the manner of death in the majority of the cases.